Training Workshop on RiceAdvice Lite for NARES and Private Sector: Delivering Site-Specific Rice Recommendations in Mali - Suh, Neville; Ahouantan, Kokou; Dossou-Yovo, Elliott (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Rice plays a vital role in Mali’s food security and rural employment, but production faces growing challenges from climate variability, poor soil fertility, and limited farmer capacity to adopt climate-smart practices. The AICCRA Mali project addresses these challenges by promoting climate-smart agriculture (CSA) tools such as RiceAdvice Lite to improve sustainable rice production. In 2025, AICCRA conducted two capacity-building sessions, training three Extension Officers and 16 Field Assistants from NARES, private sector, and multiple regions in generating site-specific fertilizer recommendations using RiceAdvice Lite. A total of 19 trainers of trainers, including six women, were equipped to support lead farmers, strengthen institutional capacity, and ensure the long-term adoption of CSA and climate information services in Mali.